2020
DOI: 10.18203/2349-2902.isj20202402
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on pattern of superficial surgical site infections in patients undergoing emergency laparotomy for perforation peritonitis

Abstract: Background: surgical site infections (SSIs) are recognized as a common surgical complication occurring in about 3% of all surgical procedures and in upto 20% of patients undergoing emergency intraabdominal procedures. Aims: To determine the incidence of SSIs in emergency laparotomies done for perforation peritonitis and the organisms involved and their sensitivity pattern in superficial SSI. The objective of the study was to determine the effect of planned intra operative intervention [antibiotic lavage with I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[15] −6% and Sharan et al[16] −7%. Few other Indian studies have stated higher incidence of SSI like Patel et al[17] −12.68%, Mekhla et al[5] −39%, and Singh and Yadalwar[7] −26.4%. This rise in incidence was secondary to the fact that they included emergency surgeries only[7] and rural setting[5].…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…[15] −6% and Sharan et al[16] −7%. Few other Indian studies have stated higher incidence of SSI like Patel et al[17] −12.68%, Mekhla et al[5] −39%, and Singh and Yadalwar[7] −26.4%. This rise in incidence was secondary to the fact that they included emergency surgeries only[7] and rural setting[5].…”
mentioning
confidence: 89%
“…Few other Indian studies have stated higher incidence of SSI like Patel et al[17] −12.68%, Mekhla et al[5] −39%, and Singh and Yadalwar[7] −26.4%. This rise in incidence was secondary to the fact that they included emergency surgeries only[7] and rural setting[5]. The previous studies have also shown lower incidence of SSI like Saravanakumar and Devi[6] −4.34%, Chada et al [4] −3.83%, and Carvalho et al [18] −3.4%, which were due to inclusion of clean or clean contaminated surgeries only [4,6].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In India, it is shown to be consistently higher, i.e., 23% to 38%, despite implementing many guidelines. SSI rates are highest in the case of abdominal surgeries when compared to other system surgeries (3), especially in emergency cases (4), with the worst being the dirty abdominal wounds (grade IV) which are reported as high up to 60% (5). Prevention of SSI is the most challenging and crucial part of patient care in the post-operative period.…”
Section: Introductionmentioning
confidence: 99%